2020
DOI: 10.1021/acs.jpcc.0c07674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Vacancies on the Mechanoluminescence Response of Magnesium Oxide

Abstract: The mechanoluminescence response of oxide materials has implications for the use of these materials in structural health monitoring applications, where crack propagation needs to be monitored. Thus, we describe the mechanoluminescence of MgO powders, showing that the signal is dependent on the existence of oxygen vacancies. Cathodoluminescence (CL) spectra of the powders exhibited an emission at 2.10 eV associated with F + centers (oxygen vacancies), as well as intense CL emissions at 3.70 and 4.10 eV, associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Eu 2+ /Eu 3+ -, Ce 3+ -, and Tb 3+ -doped HAp powders (HAp:Eu, HAp:Ce, and HAp:Tb) were synthesized by solution combustion synthesis. The reagents used were calcium nitrate tetrahydrate [Ca­(NO 3 ) 2 ·4H 2 O, 99%], ammonium hydrogen phosphate [(NH 4 ) 2 HPO 4 , 98%], and carbohydrazide [CO­(NHNH 2 ) 2 , 97%], acquired from Alfa Aesar (Ward Hill, MA). Cerium nitrate hexahydrate [Ce­(NO 3 ) 3 ·6H 2 O, 99.9%] and terbium nitrate hexahydrate [Tb­(NO 3 ) 3 ·6H 2 O, 99.9%] from Sigma-Aldrich (Burlington, MA), and europium nitrate hexahydrate [Eu­(NO 3 ) 3 ·6H 2 O, 99.9%] from Alfa Aesar were used as the sources of the rare-earth dopants.…”
Section: Methodsmentioning
confidence: 99%
“…Eu 2+ /Eu 3+ -, Ce 3+ -, and Tb 3+ -doped HAp powders (HAp:Eu, HAp:Ce, and HAp:Tb) were synthesized by solution combustion synthesis. The reagents used were calcium nitrate tetrahydrate [Ca­(NO 3 ) 2 ·4H 2 O, 99%], ammonium hydrogen phosphate [(NH 4 ) 2 HPO 4 , 98%], and carbohydrazide [CO­(NHNH 2 ) 2 , 97%], acquired from Alfa Aesar (Ward Hill, MA). Cerium nitrate hexahydrate [Ce­(NO 3 ) 3 ·6H 2 O, 99.9%] and terbium nitrate hexahydrate [Tb­(NO 3 ) 3 ·6H 2 O, 99.9%] from Sigma-Aldrich (Burlington, MA), and europium nitrate hexahydrate [Eu­(NO 3 ) 3 ·6H 2 O, 99.9%] from Alfa Aesar were used as the sources of the rare-earth dopants.…”
Section: Methodsmentioning
confidence: 99%
“…These attributes hinder their practical applications, such as pixeled sensing and display. Therefore, alternative strategies, including physical vapor deposition [23,53,54] , ultrasonic spray pyrolysis [55] , combustion synthesis [56,57] , melt-quenching approach [58] , solution synthesis [26,59,60] , suppressed dissolution approach [61] , and molten salt shielded sintering [62,63] , have been developed. For example, biphasic ZnS ML microparticles have been synthesized using an in-air molten salt shielded sintering method, eliminating the need for grinding [Figure 2A] [63] .…”
Section: Synthesis Of ML Materialsmentioning
confidence: 99%
“…More recently, Wang et al reported two triboluminescence signals centered at 420 and 475 nm for ZnS crystals, attributing them to F S + centers (sulfur vacancies containing one trapped electron) and acceptor-type zinc vacancies, respectively. We recently reported the mechanoluminescence response of MgO powders, showing a pronounced signal because of the presence of two types of oxygen vacancies, namely, F and M centers.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wang et al 17 reported two triboluminescence signals centered at 420 and 475 nm for ZnS crystals, attributing them to F S + centers (sulfur vacancies containing one trapped electron) and acceptor-type zinc vacancies, respectively. We recently reported the mechanoluminescence response of MgO powders, 18 showing a pronounced signal because of the presence of two types of oxygen vacancies, namely, F and M centers. Several researchers have found a triboluminescence response from barium hexacelsian, (BaAl 2 Si 2 O 8 , h−BAS), doped with small amounts of rare-earth ions (h−BAS:RE), including samarium, ytterbium, cerium, europium, 19,20 and dysprosium, 21 where the color of the emission can be adjusted by changing the type of rare-earth ion dopant, allowing control over the signal type such that emissions ranging anywhere from the red to the blue region of the electromagnetic spectrum can be achieved.…”
Section: Introductionmentioning
confidence: 99%